Idiopathic myelofibrosis mimicking hemolytic anemia - R Baral; G Aryal; KC Shiva Raj (Association of Clinical Pathologists of Nepal, 2012)
Idiopathic Myelofibrosis is an infrequent chronic myeloproliferative disorder characterized by varying degrees of bone marrow fibrosis and extra medullary hematopoiesis, with the fibrosis being a reactive phenomenon to a neoplastic proliferation of a pluripotent hematopoietic stem cell. Idiopathic Myelofibrosis is heterogeneous in presentation and clinical course, with anemia being one of the most important problems. We present a case of a 59 year old male who presented with severe anemia, the peripheral blood picture mimicking hemolysis with numerous schistocytes and teardrop cells. Journal of Pathology of Nepal (2012) Vol. 2, 323-327 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6888